Doxycycline residues in edible tissues of pigs - Mestorino, Olga Nora (2016)
Doxycycline (DOX) is a variant of the tetracycline antimicrobial with similar properties, but with a longer action period. It is widely used in swine production. The presence of residues of antibiotics in food products of animal origin has a special toxicological interest due to their potential effects on human health. Our aim was to evaluate the withdrawal time (WT) of DOX formulation (25%) in edible tissues of swine, after PO administration. Eighteen healthy young pigs (30-35 days old) were used. DOX was administered with drinking water during 5 days at 10 mg kg-1. Two animals, as the control group, were not treated. Four animals per group were sacrificed by exsanguination 24 hours until 11 days post-treatment. Muscle, liver, kidney and skin/fat samples were obtained. DOX was determined by HPLC with UV detection. For muscle tissue, a WT of 4.3 days was determined. In other tissues, DOX concentrations were measured until 7-11 days post-administration. The WT was 7.2, 4.9 and 4.5 days for liver, kidney and skin/fat, respectively. After administration of DOX at 10 mg kg-1 for 5 days through medicated drinking water, a WT of 8 days must be set for safe consumption of medicated animals.